2022
DOI: 10.3390/catal12080843
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Non-Noble Metal Catalysts for Oxygen Electrode in Zn-Air Batteries: A Mini Review

Abstract: Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) play crucial roles in energy conversion and storage devices. Particularly, the bifunctional ORR/OER catalysts are core components in rechargeable metal–air batteries, which have shown great promise in achieving "carbon emissions peak and carbon neutrality" goals. However, the sluggish ORR and OER kinetics at the oxygen cathode significantly hinder the performance of metal–air batteries. Although noble metal-based catalysts have been widely emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 114 publications
0
15
0
Order By: Relevance
“…The mass activities for Pt-Co/N-MC, Pt-Ni/N-MC and Pt-Ru/C is found to be 0.29, 0.53 and 0.11 mA g −1 and their corresponding i k values are 0.92, 2.01 and 0.31 mA cm −2 respectively [80][81][82][83] and shown in the 6b as the increase of the discharge current rate there is a downward shift in the discharge potential plateau is due to the low ORR reaction kinetics. 86,87 However the step-down, from low to high current shows the voltage plateau remains the same for the step-up, from high to low current also, this shows that catalyst have the enhanced mass transfer efficiency and superior electrocatalytic activity 88 6d. The Pt-Co/N-MC catalyst initially, the discharge potential at 1.32 V and charge potential at 1.96 V having the potential difference of 0.64 V, gradually stabilized and shows the voltage drop after 36 h (110 cycles, 20 min for charging and discharging in each cycle) with the 0.85 V potential gap, voltaic efficiency was calculated 57% for 100th cycle, while for Pt-Ni/N-MC shows initially, the discharge potential at 1.32 V and charge potential at 1.85 V having the potential difference of 0.53 V, the voltage drop after 30 h (90 cycles, 20 min for charging and discharging in each cycle) with the 0.76 V potential gap, the voltaic efficiency was calculated to 58% for 90th cycle.…”
Section: Resultsmentioning
confidence: 89%
“…The mass activities for Pt-Co/N-MC, Pt-Ni/N-MC and Pt-Ru/C is found to be 0.29, 0.53 and 0.11 mA g −1 and their corresponding i k values are 0.92, 2.01 and 0.31 mA cm −2 respectively [80][81][82][83] and shown in the 6b as the increase of the discharge current rate there is a downward shift in the discharge potential plateau is due to the low ORR reaction kinetics. 86,87 However the step-down, from low to high current shows the voltage plateau remains the same for the step-up, from high to low current also, this shows that catalyst have the enhanced mass transfer efficiency and superior electrocatalytic activity 88 6d. The Pt-Co/N-MC catalyst initially, the discharge potential at 1.32 V and charge potential at 1.96 V having the potential difference of 0.64 V, gradually stabilized and shows the voltage drop after 36 h (110 cycles, 20 min for charging and discharging in each cycle) with the 0.85 V potential gap, voltaic efficiency was calculated 57% for 100th cycle, while for Pt-Ni/N-MC shows initially, the discharge potential at 1.32 V and charge potential at 1.85 V having the potential difference of 0.53 V, the voltage drop after 30 h (90 cycles, 20 min for charging and discharging in each cycle) with the 0.76 V potential gap, the voltaic efficiency was calculated to 58% for 90th cycle.…”
Section: Resultsmentioning
confidence: 89%
“…Since ZABs are kinetically constrained by both ORR and OER reactions, the OER performance of Zn, Fe/NC-800 was also evaluated before assembling the ZAB. The results show that the E j =10 of Zn, Fe/NC-800 in 0.1 M KOH solution is 1.573 V (Figure S15), which is comparable with reported catalysts. , Zn, Fe/NC-800 exhibits a peak PD of 170 mW cm –2 (Figure a), which is much higher than that of Pt/C (130 mW cm –2 ) and Zn/NC (117 mW cm –2 ). In addition, the open-circuit voltage of each catalyst is provided for reference (Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…4,[10][11][12][13][14] The escalating energy consumption and the climate crisis have amplified focus on alternative green energy technologies, such as fuel cells and metal-air batteries. [15][16][17] However, these systems require active electrocatalysts to enhance the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) taking place in these devices. Currently, expensive Pt or Pt alloys on carbon carriers and RuO 2 or IrO 2 are considered the best commercial catalysts for the ORR and the OER, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most promising candidates for substituting expensive noble metal-based catalysts are carbonbased materials that are co-doped with nitrogen and transition metal(s), like Fe and Co. [23][24][25][26] Furthermore, carbon-based materials are excellent catalyst supports, due to their low cost, good electrical conductivity, durable structure, resistance to acids and bases, and good adjustability. 16,20,[26][27][28] However, the synthesis of a multifunctional catalyst material, which catalyses both reactions simultaneously, can be a great challenge due to the need for different catalytic sites and mechanisms. Pioneering work on M-N-C-type catalysts was conducted by Jasinski, who demonstrated that introducing transition metals with nitrogen into the carbon lattice through pyrolysis significantly enhances the activity of ORR electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%